Fatores de manejo na colostragem e aleitamento de bezerras leiteiras e seu impacto no desenvolvimento corporal e sanidade em fazendas de Castro - PR e região - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
In the dairy cattle production system, the raising of calves is one of the factors that most impact the cost of production, with this is expected to minimize the losses that can occur in the raising of animals, such as high rates of morbidity and mortality, and failures on body development during the milking phase. Due to the importance of this category in the future milk production and genetic improvement of the herd, the objective of this study was to evaluate the management of colostrum and milk feeding of calves, from birth to weaning, relating it to performance and health parameters. Nine dairy farms were evaluated, with an average production of 40.1 liters/cow/day, totaling 1,479 calves. Colostrum and serum Brix, volume, time, and type of colostrum supplied (fresh, frozen or enriched with colostrum replacer), weight at birth and weaning, daily weight gain, transitional milk supply, type of milking, grams of dry matter of liquid diet provided, and occurrence of diarrhea and pneumonia were analyzed. The parameters were evaluated using analysis of variance (ANOVA), with means compared using Tukey's test, and logistic regression of diseases, compared through odds ratios. Birth weight and amount of dry matter in milk were used as covariates. The quality, adequate time, volume and type of colostrum impacted the calves' serum Brix and, consequently, the susceptibility to pneumonia and diarrhea. Colostrum with Brix lower than 21% resulted in lower serum Brix (9% lower), average daily gain (ADG) (6.2% lower) and weaning weight (8.6% lower). Calves that received colostrum within 2 hours after birth had better serum Brix (3.2% higher), ADG (7.2% higher), weaning weight (7.7% higher) and fewer cases of diarrhea and pneumonia. The supply of transition milk above four days resulted in higher ADG (18.3% greater) and weaning weight (12.3% greater). The most used milk by the farms was pasteurized thickened milk, which resulted in higher ADG (12% higher) and weaning weight (1.4% higher). It can be stated that best practices in colostrum management and milking provide animals with better rates of body development and health, thereby increasing the efficiency of dairy heifer rearing, resulting in animals with greater potential for milk production in the future.
Keywords: aleitamento; colostro; desempenho animal; diarreia; pneumonia; animal performance; colostrum; diarrhea; milking; pneumonia; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA